Pola Asuh Otoriter dan Implikasinya terhadap Kehidupan Sosial Mahasiswa Makassar: Kajian Sosiologi - Atma, Atma Ras; Dimas Ario Sumilih; Nuvida RAF; Musrayani Usman; Hariashari Rahim; Andi Nurlela; Andini Aprilia Ananda (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2025)
This study aims to examine authoritarian parenting patterns and their implications for students' social identities. Using a qualitative approach with a case study strategy, this study involved six students from families who experienced authoritarian parenting. Data were obtained through in-depth interviews and thematic analysis using Max Weber's theory of social action and Pierre Bourdieu's concepts of habitus and symbolic domination. The results of the study show that authoritarian parenting patterns do not only stem from religious values and the social status of parents, but are also passed down through family social structures that are not reflective of changing times. Parenting is carried out through restrictions on freedom of expression, symbolic supervision, and the use of cultural values such as siri na pacce as a moral framework. However, in some cases, these noble values are interpreted rigidly, thereby limiting the space for dialogue between parents and children. The implications include symbolic alienation, identity crisis, and the emergence of manipulative behavior and symbolic resistance outside the home. This study emphasizes the importance of a more dialogical and adaptive parenting approach in modern social dynamics.